Characterisation of ESBL/AmpC-producing Enterobacteriaceae isolated from three poultry farms in West coast, Peninsular Malaysia - Tan, Hui Shee (2024)
Extended-spectrum beta lactamases (ESBLs) and AmpC beta-lactamases (AmpCs)-producing Enterobacteriaceae have been increasingly reported and imposing significant threat to public. Livestock production industry might be the important source for clinically important ESBL-producing Enterobacteriaceae. This study aims to investigate the resistance profile, phenotypic ESBL production, beta-lactamase genes, virulence factors, and plasmid replicon types among 59 Enterobacteriaceae strains isolated from poultry faecal samples in Malaysia’s commercial poultry farm. The identity of bacteria was determined by API and 16S rRNA sequencing. Resistance profile was determined by antimicrobial susceptibility test via disk diffusion method. ESBL production was examined via double disk synergy test. Beta-lactamase genes, virulence genes and plasmid replicons were screened using polymerase chain reaction (PCR). There were 38.7% and 32.3% of E. coli resistant to cefotaxime and cefoxitin, respectively, while Klebsiella spp. demonstrated resistance rate of 52.6% to both mentioned antimicrobials. Majority of the E. coli isolates carried blaTEM and blaCMY-2 group. blaSHV was the most prevalent genes detected in Klebsiella spp., followed by blaDHA and blaTEM. Resistance to extended spectrum cephalosporin in our isolates was primarily mediated by plasmid mediated AmpC beta-lactamase such as CMY-2 group and DHA enzyme. The CTX-M genes were found in two ESBL-producing E. coli. IncF, IncI1, and IncN plasmids were most frequently detected in E. coli and Klebsiella spp. The virulence factor, including EAST1 and pAA were identified at low frequency. This study highlights the poultry as a reservoir of resistance and virulence determinants and prevalence of plasmids in Enterobacteriaceae might drive their dissemination.